Infiltration Kinetics of Cr3C2 by Manganese Cupronickel in the Process of Obtaining Cermets - Shihab, T.A.; Paraiko, Yu.I.; Prysyazhnyuk, P.M.; Ropyak, L. Ya.; Turluch, V.V.; Kryl’, Ya.A. (Physics and Chemistry of Solid State, 2015)
A theoretical model of infiltration kinetics based on the Darcy's law which was evaluated by W − Lambert function has been established for Cu-Ni-Mn alloy (grade MNMts 60-20-20) during melt infiltration into Cr3C2 porous skeletons with different morphology. It is shown, that theoretical calculations are in good correlation with experimental data obtained by pressureless infiltration of carbide preforms with open porosity 20-40 vol. % at 1200 °C. Calculations shows that infiltration height dependence on the average size of carbide particles is described by curves with a maximum which corresponds to 60 μm for specified system with carbide skeleton porosity of 40 vol. %.